A Miniature Energy Harvesting Rectenna for Operating a Head-Mountable Deep Brain Stimulation Device - Md Kamal Hosain; Abbas Z. Kouzani; Mst Fateha Samad; Susannah J. Tye (IEEE Access, 2015)
This paper presents design, implementation, and evaluation of a miniature rectenna for energy harvesting applications. The rectenna produces DC power from a distant microwave energy transmitter. The generated DC power is then utilized to operate a head-mountable deep brain stimulation device. The rectenna consists of a miniature three-layer planar inverted-F antenna and a Schottky-diode-based bridge rectifier. The antenna has a volume of π × 6 × 1.584 mm3, a resonance frequency of 915 MHz with a simulated bandwidth of 18 MHz (907-925 MHz), and a measured bandwidth of 18 MHz (910-928 MHz) at the return loss of -10 dB. A dielectric substrate of FR-4 of εr = 4.5 and δ = 0.02 is used for simulation and fabrication of the antenna and the rectifier due to its low cost. An L-section impedance matching circuit is employed between the antenna and the rectifier to reduce the mismatch loss. The impedance matching circuit operates as a low-pass filter eliminating higher order harmonics. A deep brain stimulation device is successfully operated by the rectenna at a distance of 20 cm away from a microwave energy transmitter of power 26.77 dBm. The motivation of this paper includes creation of a deep brain stimulation device that operates indefinitely without a battery. From the application standpoint, the developed energy harvesting rectenna facilitates long-term deep brain stimulation of laboratory animals for preclinical research investigating neurological disorders.